The Meaning of Symbols in The Peucicap Aneuk Procession in Aceh: A Semiotic Study - Zulkhairi, Zulkhairi; Shaliha, Chairunnisa Ahsana Amalan; Azhari, Azhari; Zulhelmi, Anshar (Universitas Pendidikan Indonesia, 2024)
The Peucicap Aneuk tradition is part of past culture with historical value. In its implementation there are religious symbols that have their own meaning. The approach used in this research is semiotic theory to read and understand the meaning of the symbols used by the people of Aceh during the implementation of the Peucicap Aneuk procession. with descriptive qualitative research design. primary data of this research comes from field observations of the Peucicap Aneuk procession and secondary data comes from journals, books, and ancient Acehnese manuscripts. This research showed that, in general, the Acehnese people perform the Peucicap Aneuk procession in the morning on the 7th (seventh) day after a mother gives birth to her child. When the peucicap ritual is carried out, there are 17 (seventeen) symbols, namely rice and paddy, sticky rice, Tumpo, On Peusijuek, free-range chicken egg yolk, rice kneaded into porridge, honey, Zam-Zam water, fruits, chicken thighs, chicken liver, turmeric, salt, sugar, coconut, mirror, Quran. In the Peucicap Aneuk procession, this article confirms the expectations of every parent for their children through the representation of cultural symbols. This article shows that there are several relations between the role of these symbols and the spirit of the community to preserve this culture in line with Islamic values.